THE EFFECT OF OXYTOCIN MASSAGE ON FLUENCY BREASTFEEDING IN MULTIPAROUS POSTPARTUM MOTHERS IN THE WORKING AREA PUSKESMAS MEDAN JOHOR YEAR 2022 - Ndraha, Destin Murni Yanti; Sinaga, Siti Nurmawan; Simanullang, Ester; Purba, Edy Marjuang (Yayasan Nuraini Ibrahim Mandiri, 2024)
Exclusive breastfeeding in Indonesia has an achievement of 66.06% according to the Ministry of Health's 2020 research. For North Sumatra, it is 53% and exclusive breastfeeding coverage in Medan city is still low with the 9th lowest or 30.41% and IMD coverage in Medan city is 22.19%. The cause of low exclusive breastfeeding is low milk production, especially in the first day after childbirth, due to the lack of stimulation to increase oxytocin and prolactin hormones. Nonpharmacological efforts, namely oxytocin massage, can help smooth breast milk. This study aims to analyse the effect of oxytocin massage on breast milk fluency in multiparous postpartum mothers in the Medan Johor Health Centre working area in 2022. This study used quantitative research, with a Quasi Experiment research design with a Nonequivalent Control Group Design approach. Sampling technique with purpose sampling with 12 respondents for the control group and 12 respondents for the experimental group. The results of the Wilcoxon test with a p value of 0.002 showed that the p value < α (0.005) stated that there was an effect of oxytocin massage on the smoothness of breast milk in multiparous postpartum women in the Medan Johor Health Centre working area in 2022.